PERBANDINGAN KINERJA OSTBC (Orthogonal Space Time Block Code) DENGAN RATE Â½ MENGGUNAKAN MODULASI BPSK & QPSK - Yoga Perdana, Ridho Hendra (Jurnal IPTEK, 2017)
The wireless communication system is a well known and a standard technology. However, the system performance is highly dependent on the channel fading between transmitter and receiver. Therefore, there is a transmit diversity technique such as Multiple Input Multiple Output (MIMO) to reduce fading effect.One of the transmit diversity technique is Orthogonal Space-Time Block Code (OSTBC). OSTBC is a transmission channel coding technique with multiple transmitting and receiving antennas. The principle of OSTBC is to send multiple copies of the information signal from a data stream across some antennas; thus, some of the copies of data received are better than others. After combined with BPSK modulation, a compressed Bot Error Rate (BER) value at 10-3 at 5 dB Signal to Noise Ratio (SNR) was obtained, whereas after combined by QPSK modulation, a BER value at 10-3 at 7 dB SNR was obtained.